2011
DOI: 10.1017/s0950268810003092
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and epidemiological investigation of the Neisseria meningitidis serogroup A epidemic in Niger in 2009: last wave before the introduction of the serogroup A meningococcal conjugate vaccine?

Abstract: The 2009 meningitis season in Niger was characterized by an early onset, beginning in the very first weeks of the year and peaking from the 12th to the 15th week with 5655 clinical cases over the 4 weeks. From 1 January 2009 to 28 June 2009 (week 26), a total of 13,733 clinical cases of meningitis were reported to the national epidemiological surveillance system with a case-fatality rate of 4·2%. During the season 25 of the 42 health districts reached the epidemic threshold and 11 the alert threshold. Reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…8 The age distribution of NmC cases, with the highest proportions observed in adolescents and young adults, is similar to that reported in previous NmA epidemics, 22 whereas the predominance of NmW cases in children younger than 5 years has been reported in other NmW epidemics. 4,6 The overall case fatality rate of 5·9% in this NmC epidemic is consistent with that reported in several NmA, NmW, and NmX epidemics in Niger (roughly 4–8%), 4,8,2123 although the incompleteness of case outcome in the surveillance data limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…8 The age distribution of NmC cases, with the highest proportions observed in adolescents and young adults, is similar to that reported in previous NmA epidemics, 22 whereas the predominance of NmW cases in children younger than 5 years has been reported in other NmW epidemics. 4,6 The overall case fatality rate of 5·9% in this NmC epidemic is consistent with that reported in several NmA, NmW, and NmX epidemics in Niger (roughly 4–8%), 4,8,2123 although the incompleteness of case outcome in the surveillance data limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 88%
“…Although the NmC epidemic did not match the magnitude of the largest NmA epidemics in Niger (eg, the 2009 epidemic with nearly 14 000 cases reported), 21 greater numbers of cases were reported during the NmC epidemic (9367 total cases) than in the 2010 mixed NmA–NmW epidemic (nearly 3000 total cases 4 ) and the 2006 mixed NmA–NmX epidemic (more than 4000 total cases). 8 The age distribution of NmC cases, with the highest proportions observed in adolescents and young adults, is similar to that reported in previous NmA epidemics, 22 whereas the predominance of NmW cases in children younger than 5 years has been reported in other NmW epidemics.…”
Section: Discussionmentioning
confidence: 85%
“…Saharan dust, carried by the Harmattan, has been shown previously to affect health, particularly by exacerbating asthma and favoring the establishment of respiratory tract infections,25, 26, 27 and is thought to have contributed to meningitis outbreaks in Burkina Faso and Niger 3 . Previous studies have demonstrated that uptake of particulates by macrophages can disrupt phagocytic bacterial killing, 28 and we demonstrate here that dust-exposed phagocytes (both macrophages and neutrophils) are functionally impaired.…”
Section: Discussionsupporting
confidence: 49%
“…Neisseria meningitidis serogroups A and X and Streptococcus pneumoniae are the main causative agents 3, 4. Meningitis outbreaks in Niger show strong seasonality, suggesting climatic factors could play a role in disease mechanisms,5, 6, 7, 8, 9, 10 but these studies focus on all-cause meningitis, and little is known about the specific effect of climate on bacterial meningitis.…”
mentioning
confidence: 99%
“…Although the number of strains typed by MLST in our study was relatively low due to logistic constraints, and this could introduce a bias, we believe that our MLST results provide a reasonably representative picture of the different ST circulating during the epidemic seasons. Between 1995 and 1998, all Nm A isolates from Niger typed by MLST belonged to ST-5, from 1999 to 2001 to ST-7 (differing from ST-5 only at the pgm locus) [17], and from 2002 most of the isolates were ST-7 [18,19]. Serogoup A meningococci are largely clonal and all African isolates typed by the WHO Collaborating Centers for Reference and Research on Meningococci were remarkably homogeneous in their PorA (P1.20,9) and FetA (F3-1) sequences [20].…”
Section: Discussionmentioning
confidence: 99%